Efficient and economical recovery of lithium, cobalt, nickel, manganese from cathode scrap of spent lithium-ion batteries - Zhang, Jialiang; Hu, Juntao; Zhang, Wenjuan; Chen, Yongqiang; Wang, Chengyan (Journal of cleaner production, 2018)
A combined process was presented to recover valuable metals from lithium nickel cobalt manganese (NCM) cathodes of spent lithium-ion batteries. In this process, the cathode scrap was first roasted with carbonaceous reductant, and then carbonation water leaching was employed to selectively extract Li from the roasted cathodes. Finally, the obtained residue was leached in sulfuric acid solution to recover Co, Ni and Mn. A systematic investigation combining thermodynamic analysis, leaching experiments and characterization was conducted to explore the effect of operating conditions and leaching mechanism. The results indicate that the leaching of Li is significantly improved by injecting of CO2 into the leaching system, and more than 80% of Li can be leached within 10 min at a low liquid-solid ratio. High-quality Li2CO3 can be prepared from the leachate by direct evaporation. More than 96% of Ni, Co and Mn are extracted without adding reductant under the conditions of a H2SO4 dosage of 1.15 times the theoretical value, a time of 2.5 h, a temperature of 55 °C and a liquid-solid ratio of 3.5 mL g−1. The acid leaching process is more efficient and economical, which is ascribed to the transformation of the low-valence states of metals with high activity after reduction roasting. [Display omitted] •An efficient and economical process was proposed for recovering spent LIBs.•Over 85% of Li was selectively extracted at a low L/S ratio by carbonation leaching.•High-quality Li2CO3 was prepared via direct evaporation of carbonation leachate.•More than 98% of Ni, Mn and 96% of Co were leached without adding reductant.•Leaching mechanism of Co, Ni and Mn was explained by thermodynamic calculation.